The Right of Children and Wife in Custody and Their Maintenances Under Islamic and Malaysian Laws - Md Zamri Bin Omar@Yaakob (Kolej Universiti Islam Malaysia, 2022)
The research concerns about child's custody and maintenance for wife that will determine the rightful guardian for a child. This included their expenses according to Islamic and Malaysian Laws point of view and also the amount of many that a wife deserves during and after the dissolution of marriage. The methodology is mainly based on library research, by obtaining information through Internet, Journal, Magazines and others related books. The out come of this research shows that a mother entitles to raise her children after fulfilling particular requirements. Whereas, a husband is obliged to look after the maintenance of his soul mate spouse Both Islamic and Malaysian Civil Laws related to child custody is to provide sufficient welfare of the children for the their future life.